Profile of creative tourist in north-western of Portugal: An exploratory approach to creative experiences - Matos, Olga (2019)
Nowadays there is the emergence of a new type of visitors. This 'new' tourist has a new role as producer of the products and experiences that he himself consumes and is therefore called the “creative consumer” or simply a “creative tourist”. Defining the concept of creative tourism and who the creative tourists are, is not an easy task. In this sense, the present study intends to identify the profile of the creative tourist of the Northwestern Region and its motivations, as well as to understand the characteristics of the cultural/creative sector existing in that region of Continental Portugal. The theme of this research arises because there is no clear definition of the profile of who is the consumer of these creative experiences, based on national and international scientific studies. Thus, from July to December 2017, 205 questionnaires were applied to participants in the creative activities of the 5 pilot institutions corresponding to the northern region of the first call of the CREATOUR project - "Development of Creative Tourism Destinations in Small Cities and Rural Areas", in Continental Portugal. For the analysis of the data, descriptive and analytical statistics were used through the Statistical Package for Social Sciences (SPSS version 20). Based on the surveys, the profile of the creative tourist in the Northwestern region of Continental Portugal follows the trend of other investigations carried out in Portugal, namely in 2012 and 2014. From the data found and regarding marital status, 52.2% are single and 32.7% are married and demonstrate a high level of education, with 44.3% with a bachelor's or master's degree. It should also be noted that the majority of tourists, i.e. 90.2%, are from Portugal, followed by the Spanish and Brazilian tourists, (...)